A New Paradigm in Educational Supervision: Transforming Administrative Control into Professional Teacher Mentoring - Fadhilah; M Ihsan Al Fikri; Jamilus (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Educational supervision is a critical institutional mechanism for improving teacher professionalism and learning quality, yet it has long been dominated by administrative control rather than professional mentoring. This library research study analyzes the transformation of the educational supervision paradigm across three conceptual dimensions: (1) the limitations of the administrative-control paradigm, which positions teachers as evaluation objects and perpetuates top-down, compliance-oriented relationships; (2) the shift toward humanistic, collaborative, and coaching-based supervision that reconstitutes teachers as professional partners; and (3) the emergence of modern supervision as continuous professional mentoring integrating coaching, clinical supervision, peer learning, and digital tools within the framework of instructional leadership. Drawing on a systematic analysis of international and national literature from Scopus-indexed journals, policy documents, and academic texts, this study argues that supervision must be reconstructed as a process of professional humanization, empowerment, and learning quality enhancement. Practical implications are offered for school principals, supervisors, and policymakers.